(untitled) (Scientific journal of the Fergana State University, 2025)
Today, the environmental problem is one of the main issues facing humanity. The rapid development of various industries leads to the constant generation of significant volumes of toxic wastewater containing organic and inorganic pollutants, which seriously harm both people and the environment. Therefore, researching effective methods for wastewater treatment has become one of the urgent tasks for scientists worldwide. It is no coincidence that the President of the Republic of Uzbekistan, Shavkat Mirziyoyev, declared 2025 as the "Year of Environmental Protection and Green Economy." This article, based on the above facts, highlights an analysis of the resources of recent years for the synthesis of metal-organic frameworks and processes for the synthesis of 3 types of adsorbents based on iron and organic substances (Fe-BTC- iron- 1,3,5-benzenetricarboxylate- framework, MOP-235- Iron terephthalate metal-organic framework, CHCFe -coconut husk-clay-ferrate composite). Information about raw materials, parameters and stages of the adsorbent production process is provided.